Analisis Keamanan Layanan, Sistem Operasi, Kriptografi, dan Steganografi dalam Pengelolaan Informasi Modern - Akhsanul Khairi Siregar; M. Rifqy Pasha; Alif Asrovi; Fanni Rahmadayani; Muhammad Raihan Azhari (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of digital technology has significantly increased the need for stronger information security systems, particularly in digital services, operating systems, and data protection mechanisms such as cryptography and steganography. This study aims to analyze the role of service security, operating system security, cryptographic techniques, and steganographic methods in maintaining the confidentiality, integrity, and availability of information in the modern digital environment. The methodology used in this research is a literature review by examining scientific journals, reference books, and international security standards published between 2018 and 2024. The results indicate that service security protects communication processes and data exchange through authentication, authorization, and encryption. Operating system security supports access control management and minimizes exploitation risks through system hardening and regular security updates. Cryptography safeguards the confidentiality and integrity of data using symmetric and asymmetric algorithms, while steganography adds an extra layer of protection by concealing information within digital media. The study concludes that integrating these four security components can create a multilayered defense system that is more effective in mitigating cyber threats and ensuring comprehensive information protection.